Synthetic Approaches to the Total Synthesis of Tubulysin and its Fragments: A Review - Iqbal, Nosheen; Zahoor, Ameer F.; Rasool, Nasir; Khan, Samreen Gul; Akhtar, Rabia; Ahmad, Raheel (Current Organic Synthesis, 2022)
Background: Tubulysins, linear tetrapeptides, show extraordinary cytotoxicity against various cancer cells, with IC50 values in the nano or picomolar range. Due to their extremely vigorous anti-proliferative and antiangiogenic characteristics, tubulysins exhibit captivating prospects in the development of anticancer drugs. This review focuses on diverse routes for the total synthesis of natural and synthetic tubulysins as well as their fragments. Objective: The purpose of this review is to present the synthetic strategies for the development of antitumor agents, tubulysins. Conclusion: A range of synthetic pathways adopted for the total synthesis of tubulysins and their fragments have been described in this review. Synthesis of fragments, Tuv, Tup, and Tut can be accomplished by adopting appropriate strategies, such as Manganese-mediated synthesis, Ireland-Claisen rearrangement, Mukaiyama aldol reaction, Mannich process, etc. Tubulysins B, D, U, V, and N14-desacetoxytubulysin H have been prepared through Mitsunobu reaction, tertbutanesulfinamide method, Tandem reaction, aza-Barbier reaction, Evans aldol reaction, C-H activation strategies, etc. The remarkable anticancer potential of tubulysins toward a substantiate target makes them prominent leads for developing novel drugs against multidrug-resistant cancers.
Keywords: tubuvaline